2015
DOI: 10.1051/epjap/2015150214
|View full text |Cite
|
Sign up to set email alerts
|

Linearization strategies for high sensitivity magnetoresistive sensors

Abstract: Abstract. Ultrasensitive magnetic field sensors envisaged for applications on biomedical imaging require the detection of low-intensity and low-frequency signals. Therefore linear magnetic sensors with enhanced sensitivity low noise levels and improved field detection at low operating frequencies are necessary. Suitable devices can be designed using magnetoresistive sensors, with room temperature operation, adjustable detected field range, CMOS compatibility and cost-effective production. The advent of spintro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 119 publications
(150 reference statements)
0
59
0
1
Order By: Relevance
“…[6][7][8][9] Practical applications of the MI are monitoring of GMR sensor switching sensitive to proteins labeled by ferromagnetic nanoparticles (so called medical spintronics). 10,11 The method proposed in our article looks similar to MI measurements of the impedance in the magnetic field [6][7][8][9] except the high frequency ($10 GHz) microwave field in our work, instead of comparatively low frequencies in the MI experiments limited by the 10-100 MHz range. The advantage of the microwave monitoring proposed in our article is wireless detection of the stable states of the GMR devices and possibility to study anisotropy of their magnetoresistance.…”
mentioning
confidence: 72%
“…[6][7][8][9] Practical applications of the MI are monitoring of GMR sensor switching sensitive to proteins labeled by ferromagnetic nanoparticles (so called medical spintronics). 10,11 The method proposed in our article looks similar to MI measurements of the impedance in the magnetic field [6][7][8][9] except the high frequency ($10 GHz) microwave field in our work, instead of comparatively low frequencies in the MI experiments limited by the 10-100 MHz range. The advantage of the microwave monitoring proposed in our article is wireless detection of the stable states of the GMR devices and possibility to study anisotropy of their magnetoresistance.…”
mentioning
confidence: 72%
“…For TC 1.2, the saturation field 2μ0Hsat around 0.08 mT was demonstrated by combining the sensor with a Conetic MFC (gain: ~77 times) in 2011 [243]. In 2015, a factor of 400 times MFC was reported for an MTJ bridge [315]. In 2017, Valadeiro et al reported a high gain (~400 times) MFC with a double layer architecture [310].…”
Section: A Sensitivitymentioning
confidence: 99%
“…A linear variation of the GMR resistance with the magnetic field with a low hysteresis is obtained when the easy magnetization axis of the free layer is set perpendicular to the pinned layer. This is achieved through the shape anisotropy 27 by patterning the yoke arm length perpendicular to the pinned layer magnetization as shown in Figure 2(a). The sensor magnetoresistance evolution with the number of GMR repetitions and constant width w= 4 µm is shown in Figures 2(b-c).…”
Section: A Experimentsmentioning
confidence: 99%